Tobacco-related knowledge following a comprehensive tobacco-free workplace program within behavioral health facilities: Identifying organizational moderators. Issue 9 (September 2019) - Garey, Lorra; Neighbors, Clayton; Leal, Isabel Martinez; Lam, Cho Y.; Wilson, William T.; Kyburz, Bryce; Stacey, Tim; Correa-Fernández, Virmarie; Williams, Teresa; Zvolensky, Michael J.; Reitzel, Lorraine R.
Highlights: Training on tobacco increases related knowledge among behavioral health providers. Organization-level motivation and structure moderate training effectiveness. Change requirements, availability of resources, and client contacts moderates staff gains. Perceived value of change and client contacts moderates clinician gains. Abstract: Objective: Although smoking prevalence rates among behavioral health consumers is nearly five times that of the general population, evidence-based policies and practices to address tobacco use are uncommon within behavioral health settings. This study assessed changes in non-clinical, general staff and clinician tobacco-related knowledge following brief education provided as part of a comprehensive tobacco-free workplace program implementation and explored organizational moderators of pre- to post-education knowledge change. Methods: Fifteen behavioral health facilities, comprising hundreds of individual clinics in Texas, participated in a one (for general staff) or two (for clinicians) hour educational session. Results: There were large effect sizes in general staff knowledge gain within each consortium, and large effect sizes in clinician knowledge gain in all but one consortium. Knowledge of the requirements for change, perceived availability of resources, and total number of client contacts moderated general staff knowledge gain. Value in the change and total number of client contacts moderated training effectiveness among clinicians. Conclusions: We conclude that a brief tobacco-related education for behavioral health employees was effective in increase attendee knowledge. Practice implications: Attention to organization-level factors moderating knowledge gain has the potential to guide and improve program implementation.